Presence of Middle Cerebellar Peduncle Sign in FMR1 Premutation Carriers Without Tremor and Ataxia - Famula, Jessica L.; McKenzie, Forrest; McLennan, Yingratana A.; Grigsby, James; Tassone, Flora; Hessl, David; Rivera, Susan M.; Martinez-Cerdeno, Veronica; Hagerman, Randi J. (Frontiers in Neurology, 2018)
Abstract Here we report five cases of male FMR1 premutation carriers who present without clinical symptoms of the fragile X-associated tremor/ataxia syndrome (FXTAS), but who on MRI demonstrate white matter hyperintensities in the middle cerebellar peduncles (MCP sign) and other brain regions, a rare finding. MCP sign is the major radiological feature of FXTAS; it is therefore remarkable to identify five cases in which this MRI finding is present in the absence of tremor and ataxia, the major clinical features of FXTAS. Subjects underwent a detailed neurological evaluation, neuropsychological testing, molecular testing, and MRI evaluation utilizing T2 imaging described here. Additional white matter disease was present in the corpus callosum in four of the five cases. However, all cases were asymptomatic for motor signs of FXTAS.